The health effecs of using solarium - Kapka-Skrzypczak, Lucyna; Krasowska, Ewelina; Skrzypczak, Maciej (Polish Journal of Public Health, 2011)
Although visiting solarium seems to be safe and quite nice, it can cause serious health problems. World Health Organization placed the exposure to artificial sources of UV radiation used in tanning beds in the highest cancer risk category “carcinogenic to humans.” UV rays pose significant danger to teens and kids. There is scientific evidence that each of the three main types of skin cancer, basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and melanoma (MM) can be caused by UV exposure. It is observed that the number of new skin cancer cases continues to grow every year. This article presents actual data from different countries about the increasing number of melanoma and other skin cancers cases. It also highlights the hazard associated with UV exposure and describes health effects of UV radiation on the skin.